(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The rapid development of 3D bioprinting technology has opened up new frontiers in regenerative medicine and tissue engineering, enabling the creation of complex biological structures for therapeutic applications. Despite its promising potential, the bioprinting process is fraught with errors and shortcomings that can compromise the integrity and functionality of the printed constructs.